STRATEGI MNEMONIC UNTUK PENINGKATAN PRESTASI BELAJAR IPS SISWA KELAS VI SEKOLAH DASAR (Studi Eksperimen Terhadap Siswa Kelas VI SDN Sinarjati Tahun Pelajaran 2015/2016) - Wasmana Wasmana (STKIP Siliwangi, 2017)
Learning achievement in this research is the acquisition value of evaluations of students in social studies. The main problem in this research whether mnemonic strategies can improve student learning achievement in social studies class VI SDN Sinarjati. The main objective of this research is to improve learning achievement IPS using mnemonic strategies. The method used to solve the problems of this research using an experimental method. Researchers designed this study into two stages: a preliminary study and application of mnemonic strategies. The instrument used to collect data increase learning achievement IPS that the questionnaires and evaluation sheets. Data were netted from the researcher's analysis instrument by measuring symptoms roman center with average and variance analysis with a standard deviation formula. These results indicate that the achievement of social studies in experimental class is higher than the control class indicated by the average value of the evaluation. Acquisition of the average value of the material in the Indonesian archipelago with the first letter on the method of experimental classes 66.9 85.5 while the control class, foreign ministers of ASEAN countries by using keywords in the experimental class 61.9 to 92.7 while the control class, materials continent in the world with locations in class experimental method 95.5 64.3 while the control class, the material wonders of the world with a method to connect at 96.2 whereas the experimental class control class 66.9, material capital of the ASEAN countries with pegs on the class experimental method 95, 5 whereas 69.3 and material control class currency ASEAN countries with a story to the class experimental method 95.0 68.6 while the control class. Besides the standard deviation of the experimental class is higher than the control class, it shows that the values obtained in the experimental class are more varied than the control class. Based on these results the researchers recommend for teachers to apply mnemonic strategies in the hope students can improve academic achievement.